Biomimetic Convex Implant for Corneal Regeneration Through 3D Printing. Issue 11 (12th February 2023) - Xu, Yingni; Liu, Jia; Song, Wenjing; Wang, Qianchun; Sun, Xiaomin; Zhao, Qi; Huang, Yongrui; Li, Haochen; Peng, Yuehai; Yuan, Jin; Ji, Baohua; Ren, Li
Abstract: Blindness caused by corneal damage affects millions of people worldwide, and this number continues to rise. However, rapid epithelization and a stable epithelium process are the two biggest challenges for traditional corneal materials. These processes are related to corneal curvature, which is an important factor in determination of the corneal healing process and epithelial behavior during corneal damage. In this study, smooth 3D‐printed convex corneal implants based on gelatin methacrylate and collagen are generated. As epithelium distribution and adhesion vary in different regions of the natural cornea, this work separates the surfaces into four regions and studies how cells sense topological cues on curvature. It is found that rabbit corneal epithelial cells (RCECs) seeded on steeper slope gradient surfaces on convex structures result in more aligned cell organization and tighter cell‐substrate adhesion, which can also be verified through finite element simulation and signaling pathway analysis. In vivo transplantation of convex implants result in a better fit with adjacent tissue and stronger cell adhesion than flat implants, thereby accelerating corneal epithelialization and promoting collagen fibers and neural regeneration within 180 days. Taken together, printed convex corneal implants that facilitate corneal regeneration may offer a translational strategy for the treatment of corneal damage. Abstract : A smooth surface corneal material with curvature is prepared by 3D printing to promote corneal stroma regeneration and corneal function recovery. The results show convex cornea can induce cell alignment and promote epithelial adhesion, making repair faster and more firmly. 3D printing accompanied with mechanism research provide a new idea for the design of corneal repair materials.